Integration sites of blaCTX−M−1 relate to IncI1 plasmid phylogeny in Salmonella isolates from non-human sources in Germany - Atxaerandio-Landa, Aitor; Borowiak, Maria; Groger, Angelina; Irrgang, Alexandra; Malorny, Burkhard; Szabo, Istvan; Fischer, Jennie (Frontiers in Microbiology, 2026)
Antimicrobial resistance to cephalosporins in Enterobacterales is commonly mediated by extended-spectrum β-lactamases (ESBL). The ESBL-encoding gene most frequently detected in Salmonella isolates from livestock and the second most frequently detected in Salmonella isolates in humans in Germany is the blaCTX−M−1 gene. In this study, we characterize ESBL-producing Salmonella enterica collected from non-human sources in Germany, with a particular focus on blaCTX−M−1 harboring IncI1 plasmids. Therefore, a total of 95 blaCTX−M−1 positive isolates (S. Derby, S. Infantis, and S. Typhimurium/1,4,[5],12:i:-) from food and animal origin were investigated using short and long-read Whole-Genome Sequencing (WGS) with subsequent in-depth characterization and phylogenetic analysis of the samples and associated mobile genetic elements. WGS revealed a diverse population of blaCTX−M−1-producing S. enterica isolates in German food and animal samples. In 66 of the 95 isolates, an IncI1 plasmid could be detected. A total of 38 IncI1 positive isolates were selected for long-read sequencing to confirm the location of blaCTX−M−1 on the IncI plasmid. Additionally, to our 38 blaCTX−M−1 harboring IncI plasmids, further blaCTX−M−1 harboring IncI plasmids (n = 103) from the Plasmid Library Search Database (PLSDB), derived from different host bacteria, isolation sources, and geographical locations, were analyzed in detail to gain a deeper insight into IncI1 plasmid evolution. Results revealed that the blaCTX−M−1 gene was associated with the ISEcp1 transposable element in all but two cases. A total of six distinct integration sites (ISts) were detected across 141 IncI1 plasmids studied here. The integration sites correlated with the plasmid ST and the plasmid phylogeny, regardless of the sample origin, host bacterium, or Salmonella serovar. In conclusion, the emergence of serovar-specific or geographically restricted CTX-M-1 encoding IncI1 plasmids appears to play a minor role. In contrast, evidence suggests that a few successful IncI1 plasmid lineages/plasmid ST types are the primary vehicles for blaCTX−M−1 gene transmission in Salmonella isolates from diverse geographical origins and sources along the food production chain in Germany.